2011
DOI: 10.2319/050610-246.1
|View full text |Cite
|
Sign up to set email alerts
|

Tooth size discrepancies in Irish orthodontic patients among different malocclusion groups

Abstract: The prevalence of anterior tooth size discrepancies in this sample of Irish orthodontic patients was 37.9%. There were no statistically significant differences in the prevalence of mean overall TSDs with regard to malocclusion or gender. In the male group, the mean anterior tooth size ratio was higher in Class III and in Class II division 2 malocclusion than in Class II division 1 and higher in Class II division 2 malocclusion than in Class I malocclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 27 publications
12
53
0
1
Order By: Relevance
“…We were unable to find any statistically significant differences in the mean overall and anterior tooth size ratios between the different malocclusion groups. This is in accordance to Uysal and Sari [17] who identified no differences in tooth size ratios between malocclusion groups in a Turkish population, also in accordance to O'Mahony and Millett [11] who identified no statistical difference in tooth size ratios between malocclusion groups in an Irish population, but contrasts with Nie and Lin [12] who identified a higher prevalence of increased overall tooth size ratios in Class III malocclusions compared to Class I and Class II malocclusions in a Chinese population.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We were unable to find any statistically significant differences in the mean overall and anterior tooth size ratios between the different malocclusion groups. This is in accordance to Uysal and Sari [17] who identified no differences in tooth size ratios between malocclusion groups in a Turkish population, also in accordance to O'Mahony and Millett [11] who identified no statistical difference in tooth size ratios between malocclusion groups in an Irish population, but contrasts with Nie and Lin [12] who identified a higher prevalence of increased overall tooth size ratios in Class III malocclusions compared to Class I and Class II malocclusions in a Chinese population.…”
Section: Discussionsupporting
confidence: 84%
“…Bishara [8] found that males have larger teeth than females. Despite the difference most studies have found that there is little impact of gender on interarch ratios [8][9][10][11][12][13]. Smith et al found that males had a larger ratio than females but the differences were small and much less than one SD from Bolton norms [14].…”
Section: Journal Of Orthodontics and Endodontics Issn 2469-2980mentioning
confidence: 99%
“…To evaluate this relationship, various linear measurements by sliding calipers and digital models have been used 3,14,[16][17][18][19] . Digital dental models were considered as a valid and reliable tool for different tooth size measurements 17,19,20,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Linear measurements have been incorporated into various dental model analyses to help the clinician to measure the tooth size and tooth size discrepancies to establish the most appropriate treatment plan [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Plaster casts, whose importance has been widely supported by many authors, are generally used for the analysis and treatment of agenesis. Currently, the use of three‐dimensional (3D) images of cast models has increasingly become a relevant tool in the diagnostic and treatment of several clinical dental conditions …”
Section: Introductionmentioning
confidence: 99%